Ottoman figurative arts. - And, Metin, 1927-2008. (İstanbul)
247 sayfa
Keywords: “Coining the phrase 'bazaar painters' in a 1985 article, Metin And enriched our art history terminology with a new concept as well as offer a glimpse into the world of these artists: how they worked, what they drew, where their works are today and how they contribute to our study of history of art and culture. He continued to promote and popularise their work through books and articles published until 2007, at times repeating earlier content as required. Bazaar painters and their work were not initially identified as a distinctive genre; Franz Taeschner, the first researcher to publish a selection, felt no need to refer to them as anything other than 'miniatures'. Challenging this trend, Metin And set about the immensely difficult task of obtaining pictures of bazaar painting albums from four corners of the globe in order to illustrate a prolific series of essays and books. The second volume of Ottoman Figurative Arts, Bazaar Painters consists of twelve articles published between 1985 and 2007, a comprehensive introduction by Tülün Değirmenci, and a concise album. The pictures and inscriptions Metin And chased enthusiastically all his life are but the echoing footsteps of a book, one that was either never written, or somehow got lost before it could be published.” --